Adhyayan and Adhyapan Skill in Ayurveda on Modern Perspectives - Shankar, Hari; Dixit, Mahesh; Meena, Hari Mohan; Meena, Namo Narayan (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is a traditional Indian system of medicine. India has a long and illustrious history in the fields of knowledge and education. At both the national and international level, the relevance of ancient sciences such as Ayurveda and Yoga is being recognised and appreciated. Even today teaching and learning are two sides of the same coin. Ayurvedic education now a day is mostly concerned with exam-oriented "teaching and learning." Students’ curiosity, inquiry, inventiveness, and feedback are discouraged in the popular "factory style" education system which is also known as "direct teaching." Ayurveda rarely employs novel teaching and learning methods aimed at fostering creativity and critical thinking. The terms Adhyayan (learning) and Adhyapan (teaching) are used interchangeably in the education system. Gurukul and Guru Shishya parampara were a part of India’s ancient education system, which was followed in Ayurveda also. The current educational system has been combined with new tools and technologies that are being used in Ayurveda teaching and learning. Listening and reading, observing and imitating, and doing are examples of modern learning methods, while lecture, discussion, demonstrations, field excursions, panel discussions, group discussions, and question-answer sessions are examples of teaching methodologies. There is enough evidence in the ancient texts to suggest that most of these learning and teaching approaches existed in their earliest incarnations in the ancient times. The purpose of this work is to provide a critical review of ancient and current Ayurvedic teaching and learning techniques.